… Literaturelessness …. Issue 1 (April 2019) - Callus, Ivan
Abstract : To keep things simple, doubtless simplistic: what would it mean to take literally the term post-literary, which features in CounterText 's subtitle? What possible consequence, or conceptual advantage, could there be for literary criticism if it countenanced, even as a thought-experiment and in suppression of the reflex for problematisation of the question, the idea of the condition of being past, or without, literature? The sophistication of literary criticism and theory on anything bearing the prefix post- is well established and has determined various important moves within these discourses. But it could be contended that there might be some edge in an experiment suspending that manner of response in favour, however briefly, of a more artless probing of how and why literature-less conditions – and they do exist – bear scrutiny. Inevitably, there will be some contrivance in the affectation of that artlessness, but this is itself not without point. Accordingly, the article considers some hypothetical and some not so hypothetical situations for a literature-less condition. The assumption is that specifying them, however briefly, can be revealing – and one aspect that emerges is that there are long histories of the condition, sufficient to vindicate reflection on taking the post-literary literally and on what might hang on that.